Sñan rgyud rig pa gcer mthon : Bon-po oral transmission precepts granted by Srid-pa-rgyal-mo to Bon-zig Khyun-nag - Bon-źig Khyuṅ-nag, 1103-1183 (Tibetan Bonpo Monastic Centre, 1972)
Esoteric ritual and meditational practices of Bon.